Repeated high-speed running in elite female soccer players during international competition. Issue 2 (3rd April 2019) - Datson, Naomi; Drust, Barry; Weston, Matthew; Gregson, Warren
ABSTRACT: Objectives: To provide a detailed analysis of the repeated high-speed demands of competitive international female soccer match play.Methods: A total of 148 individual match observations were undertaken on 107 outfield players in competitive international matches, using a computerised tracking system (STATS, Leeds, England). High-speed activity was classified as either sprint activity (SA) (>25.1 km h -1 ) or high-speed running (HSR) (>19.8 km h -1 ). Repeated sprint activity (RSA) was defined as a minimum of two sprints with < 20 s recovery between sprints and repeated high-speed activity (RHSA) was defined as a minimum of two high-speed runs or sprints with < 20 s recovery between efforts.Results: HSR bouts occurred ~5 times more frequently than SA bouts. Central defenders (CD) completed ~50–80 fewer HSR bouts (moderate count ratio (CR): range 0.61–0.70) and ~10–20 fewer SA bouts (moderate CR: range 0.53–0.69) than all other playing positions. RSA bouts occurred less frequently than RHSA bouts (33 ± 10 vs. 1.1 ± 1.1).Conclusion: Consideration of both RHSA and RSA bouts is necessary to ensure a comprehensive understanding of the demands of female match play. Practitioners can utilise this information to construct position-specific training and testing programmes.